Non-invasive contrast enhancement for retinal fundus imaging - Hani, A.F.M. (2013)
Diabetic Retinopathy (DR) is vision loss impairment due to complication arising from diabetic condition affecting the retina. It is known that the foveal avascular zone (FAZ) enlarges with progression of DR due to the loss of capillaries in perifoveal capillary network. However, normal retinal fundus images suffer from low and varied contrast problems. A non-invasive digital image enhancement technique called RETICA has been developed that overcomes the problem of varied and low contrast in fundus images. RETICA first normalises the varied contrast using a Retinex-based method that separates the illumination from the reflectance part of the image followed by ICA that forms the original retinal pigment makeup namely the macular, haemoglobin and melanin retinal pigment. The technique has been applied on our FINDeRS dataset contained 175 fundus images and another 35 fundus image pairs obtained from an earlier study containing colour fundus images and their corresponding fluorescein fundus angiogram (FFA) images. For the 35 image pairs, RETICA achieved an average contrast improvement factor (CIF) of up to 5.46 compared to the invasive FFA at 5.12. For the FINDeRS images, RETICA achieved an average CIF of 5.63 with denoising. The RETICA image enhancement technique potentially reduces the need for the invasive fluorescein angiogram in DR assessment. Â© 2013 IEEE.